Analysis on Problems and Strategies of Web-based Autonomous Learning in English Courses of Open Education - Zhou, Yuanyuan (Journal of Research in Vocational Education, 2024)
With the rapid development of network technology, it puts forward greater requirements on autonomous learning ability in English courses of open education. Based on the problems in autonomous learning in English courses of open education, the thesis analyses the developmental strategies of enhancing autonomous learning abilities in English online courses of open education.